Phylogenetic signature of light and thermal stress for the endosymbiotic dinoflagellates of corals (Family Symbiodiniaceae) - Michael P. Lesser (Limnology and Oceanography, 2019)
Coral reefs around the world have been affected by a climate‐change induced phenomenon known as “coral bleaching,” which is caused by the interaction between high irradiance and elevated seawater temperatures, and involves the mass expulsion of Symbiodiniaceae from anemones, sponges, and corals. The primary drivers of this phenomenon are the inherent genetic variability in the Family Symbiodiniaceae, and the variability in the abiotic environment for variables such as irradiance and temperature. Recent experiments have either disregarded the important interactive role of irradiance or have suggested that photooxidative stress is not a prerequisite for coral bleaching because certain reactive oxygen species (ROS) can be produced in the dark. Here, fluorescent probes are used as proxies for the relative concentration of ROS in different genera of cultured Symbiodiniaceae under varying thermal and light conditions. The results show that taxon‐specific patterns of the concentration of ROS are observed but that all genera tested produced significantly greater amounts of superoxide radicals and hydrogen peroxide, compared to singlet oxygen, when exposed to high light and thermal stress. These results are contextualized in relation to the primary drivers of ROS production and the photo‐physiological basis for differences in ROS production that may then be correlated with symbiont driven coral bleaching.